The Barriers to Implementing National Spatial Data Infrastructure in Pakistan: Policy and Legislation Context - Ali, Asmat; Hussain, Hammad; Fatima, Rida; Ahmad, Munir (Journal of Public Policy Practitioners, 2024)
In today’s world, information is the most valuable resource. Geospatial information, which refers to the location of various features on earth, plays a crucial role in policymaking, implementation, and monitoring the policy outcomes. The information about forests, roads, water bodies, health and education facilities, population, human settlements etc. is geospatial. Due to financial and human resource constraints a single government department cannot collect such diverse information. Therefore, each department is mandated to collect and maintain one particular type of information. The information collected is used as evidence in policymaking and to ensure its efficacy, various types of information collected by departments is integrated and utilized. The dilemma is, government departments often do not share their collected information, despite them being funded by public money. Consequently, informed decision-making is hampered. The reasons for non-sharing of the information may include lack of technical capacity, fear of loss of control over information assets, poor quality of the information and lack of legal and policy framework to share information.  This article focuses on policy and legal barriers to geospatial information sharing in Pakistan. The study follows content analysis method, specifically used for deriving relevant information from the data. The data is collected through reviews of policy documents, minutes of meetings, and focused group discussions with experts on the subject. The article discusses how the current provisions are inadequate to deal with new developments in geospatial information sharing, and proposes recommendations for amending and updating existing laws and policies. The study finds that policymakers in Pakistan are still not aware of the potential of geospatial information and its sharing through NSDI for informing, and implementing public policies. Accordingly, the study recommends approving NSDI Act at the earliest.